2020
DOI: 10.1128/aac.02571-19
|View full text |Cite
|
Sign up to set email alerts
|

Time above the MIC of Piperacillin-Tazobactam as a Predictor of Outcome in Pseudomonas aeruginosa Bacteremia

Abstract: Pseudomonas aeruginosa bacteremia is an infection associated with a high mortality rate. Piperacillin-tazobactam is a β-lactam–β-lactamase inhibitor combination that is frequently used for the management of Pseudomonas aeruginosa infections. The pharmacokinetic-pharmacodynamic index associated with in vitro maximal bacterial killing for piperacillin-tazobactam is the percentage of the time between doses at which the free fraction concentration remains above the MIC (%fT>MIC). However, the precise %fT>MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection [1,2]. Emerging evidence suggests that in patients with sepsis, insufficient antibiotic exposure, defined as failure to meet the pharmacokinetic/pharmacodynamic (PK/PD) target to kill or inhibit the growth of a pathogen, is associated with worse clinical outcomes [3][4][5]. Previous studies demonstrated that up to 50% of critically ill patients receiving a β-lactam antibiotic with regimens based on the manufacturers' recommendations fail to reach the target [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection [1,2]. Emerging evidence suggests that in patients with sepsis, insufficient antibiotic exposure, defined as failure to meet the pharmacokinetic/pharmacodynamic (PK/PD) target to kill or inhibit the growth of a pathogen, is associated with worse clinical outcomes [3][4][5]. Previous studies demonstrated that up to 50% of critically ill patients receiving a β-lactam antibiotic with regimens based on the manufacturers' recommendations fail to reach the target [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Our new approach was forming an outcome group that the effect of antibiotic therapy is not masked by other measures and influences. A similar approach was recently performed by Tannous et al to predict the outcome of patients infected with Pseudomonas aeruginosa and treated with piperacillin-tazobactam [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[OR] 7.74, 95% confidence interval [CI] 1.31-45.2). 25 Compared with in vivo murine infection models, slightly higher fT>MIC exposures have been reported to be required to achieve clinical end points for carbapenems during patient studies. Li et al 26 identified meropenem fT>MIC of 54% was associated with microbiological eradication during the regulatory studies for lower respiratory tract infections.…”
Section: >6088% Ft>mic Was Associated With Improved Survival (Odds Rmentioning
confidence: 99%
“…In 79 patients treated with piperacillin‐tazobactam for P . aeruginosa bacteremia, >60.88% f T>MIC was associated with improved survival (odds ratio [OR] 7.74, 95% confidence interval [CI] 1.31–45.2) 25 …”
Section: β‐Lactam Pharmacodynamics: What Target Do We Aim For?mentioning
confidence: 99%